Peer Feedback, English Public Speaking Self-Efficacy, and Performance in Facebook and Brightspace - Lucia Urena-Rodriguez; Victoria L. Lowell; Weijian Yan (Education Sciences, 2025)
Social media applications (SMAs) stand at the forefront of emerging technologies in language education due to their transformative potential to enhance English speaking skills. Unlike traditional tools, SMAs leverage features like real-time communication, multimedia integration, and global connectivity, fostering authentic, meaningful interactions in socially engaging environments. Although learning management systems (LMSs) such as Brightspace have been predominantly used to conduct English language learning activities, including peer feedback, SMAs like Facebook offer unique affordances that may further promote student engagement and confidence. Developing public speaking skills is critical for effective communication in English language education; however, many students struggle with self-efficacy, speaking anxiety, and providing meaningful feedback to peers. Given the potential benefits of SMAs, this study explored their comparative impact on three dimensions of English language learning: English public speaking self-efficacy, peer feedback self-efficacy, and English speaking performance. This quasi-experimental study used a pretest–posttest design with undergraduate students (n = 15) at a large Midwestern university in the United States. Independent sample t-tests were conducted to compare outcomes between the Facebook and Brightspace groups. The results revealed that both SMAs and LMSs were equally effective platforms for peer feedback activities, with no significant differences found between groups across the three targeted areas of learning.